Professional Development and its Relationship with some Variables in the Light of Sullivan Theory among Male and Female Teachers in the Basic Education Schools in Sultanate of Oman: سالم بن ناصر بن سعيد الكحالي (Journal of the College of Education for Women, 2021)
The study aims to reveal the level of professional development in basic education schools from the male and female teachers’ viewpoint in the Sultanate of Oman. It further aims to examine its relationship with some variables in light of Sullivan theory, and the differences in the level of professional development (teachers’ skills, professional participation, professional development problems) according to the gender variable, and the educational stage (first cycle/ second cycle). The study sample consisted of (93) teachers distributed as such: (46) male teachers, and (47) female teachers. A questionnaire was prepared and applied to measure the level of the professional development of the male and female teachers. The questionnaire consisted of (45) paragraphs. The researcher analyzed the means, standard deviations, and (T) test. Results have shown that that there is a high level of professional development among male and female teachers in the basic education schools in the Sultanate of Oman. Moreover, the dimensional levels have come first after teachers’ skills, second after professional participation, and third after professional development problems. Further, there are no statistically significant differences attributed to the gender and the educational stage variables (first cycle/ second cycle). The study has recommended the importance of benefiting from the applications of psychology and its theories in building, and developing the personalities of male and female teachers and in education sector’s professionals professionally, scientifically, socially, psychologically and academically. It has also recommended to encourage male and female teachers to pursue postgraduate studies and employ procedural research in electronic training and professional development operations.